2001
DOI: 10.1039/b100457n
|View full text |Cite
|
Sign up to set email alerts
|

Probing temperature-dependent behaviour in self-assembled monolayers by ac-impedance spectroscopy

Abstract: Gold electrodes modiÐed by monolayers of three di †erent long-chain thiol derivatives were studied by electrochemical impedance spectroscopy with a redox probe over a wide temperature range. [Fe(CN) 6 ]4~@3T he impedance characteristics of a bare gold electrode are compared to those of the same electrode modiÐed with n-hexadecanethiol, n-octadecanethiol, and 11-mercaptoundecanoic acid, all between 15 ¡C and 65 ¡C. A strong temperature dependence of the ÐlmsÏ electrical features was observed. All Ðlms show mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 14 publications
(2 reference statements)
1
26
0
Order By: Relevance
“…Thermal stability studies of thiol monolayers have been reported by various groups [19,20,[27][28][29][30][31][32][33][34][35]. Bensebaa and coworkers observed two kinds of transitions; the first transition is between two ordered phases that differ in the tilt direction [19b,19c].…”
Section: Comparative Thermal Stability Of Thiol and Diselenide Monolamentioning
confidence: 99%
“…Thermal stability studies of thiol monolayers have been reported by various groups [19,20,[27][28][29][30][31][32][33][34][35]. Bensebaa and coworkers observed two kinds of transitions; the first transition is between two ordered phases that differ in the tilt direction [19b,19c].…”
Section: Comparative Thermal Stability Of Thiol and Diselenide Monolamentioning
confidence: 99%
“…Recently AC impedance spectroscopy has been used to probe the temperaturedependent phase transition of the SAMs on a gold surface [143]. This technique involves the measurement of the frequency dispersion of the impedance or admittance of a system.…”
Section: Electrochemical and Electrical Propertiesmentioning
confidence: 99%
“…The formation of a disordered monolayer at deposition or observation temperature higher than the phase transition is manifested by a change in wettability, thickness of the monolayer, of vibrational frequency, and electron transfer properties. 21,22,32,33,[35][36][37] Also, the phase transition induces a nonreversible change of molecular structure in the timescale of the experiments, previously reported to be at least two weeks. 22 This article aims at answering these questions for IL-SAM: do IL-SAM undergo the same phase transition as organic SAM and how does deposition temperature influence the properties of resulting IL-SAM?…”
Section: Resultsmentioning
confidence: 84%
“…The electrochemical properties of a neutral alkyl thiol selfassembled monolayer depend on the deposition temperature. 21,22 For example, C 16 and C 18 alkyl chain thiols are insulating below a critical deposition temperature. Above the critical deposition temperature, the monolayers exhibited increased electron transfer as measured with Fe(CN) 6 4À/3À…”
Section: Introductionmentioning
confidence: 99%